2004
DOI: 10.5194/angeo-22-1177-2004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous HF measurements of E- and F-region Doppler velocities at large flow angles

Abstract: Abstract. Data collected by the CUTLASS Finland HF radar are used to illustrate the significant difference between the cosine component of the plasma convection in the F-region and the Doppler velocity of the E-region coherent echoes observed at large flow angles. We show that the E-region velocity is ∼5 times smaller in magnitude and rotated by ∼30 • clockwise with respect to convection in the F-region. Also, measurements at flow angles larger than 90 • exhibit a completely new feature: Doppler velocity incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 23 publications
(35 reference statements)
6
40
0
Order By: Relevance
“…6d), therefore, HF Doppler velocity limited in magnitude is unlikely to be caused by the small electric field intensity. The Doppler velocity at HF was featured recently in another study (Makarevitch et al, 2004), where the same conclusion was reached on the basis of the simultaneous Fand E-region CUTLASS observations during the event when the DMSP drift-meter measurements did not show any significant latitudinal variation of the convection component. Therefore, we will not discuss this issue any further, but note that the simultaneous HF/VHF observations provide yet another argument in support of this conclusion.…”
Section: Irregularity Doppler Velocity and Electrojet Directionsupporting
confidence: 53%
“…6d), therefore, HF Doppler velocity limited in magnitude is unlikely to be caused by the small electric field intensity. The Doppler velocity at HF was featured recently in another study (Makarevitch et al, 2004), where the same conclusion was reached on the basis of the simultaneous Fand E-region CUTLASS observations during the event when the DMSP drift-meter measurements did not show any significant latitudinal variation of the convection component. Therefore, we will not discuss this issue any further, but note that the simultaneous HF/VHF observations provide yet another argument in support of this conclusion.…”
Section: Irregularity Doppler Velocity and Electrojet Directionsupporting
confidence: 53%
“…Several studies showed that the SuperDARN E region velocity is well below the E×B component along the radar beam (e.g., Makarevitch et al, 2004;Koustov et al, 2005). However, usually, the amount of E-region echoes is not large enough to strongly affect the CPCP estimates.…”
Section: Discussionmentioning
confidence: 99%
“…• Population ii echoes have u los values which appear proportional to v los (that is, a flow angle behaviour that is roughly a cosine dependence) with a constant of proportionality close to *0.2 (Milan et al 2003a;Makarevitch et al 2004;Koustov et al 2005). …”
Section: E-region Ionospheric Irregularitiesmentioning
confidence: 99%
“…This usually has to be inferred, with wide margins of uncertainty. In an attempt to overcome this, effort has been made to compare echo characteristics with F-region backscatter (Milan and Lester 1998;Makarevitch et al 2004), incoherent scatter radar measurements (Makarevitch et al 2006), or low-altitude spacecraft measurements . In addition, there has been comparison of echo characteristics at widely differing frequencies, for instance in the HF and VHF bands (e.g.…”
Section: E-region Ionospheric Irregularitiesmentioning
confidence: 99%